2019
DOI: 10.1002/ccd.28415
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in patients undergoing endovascular therapy for critical limb ischemia

Abstract: Background Similar to coronary angiography and interventions, patients undergoing percutaneous treatment of lower extremity peripheral arterial disease are also at risk of acute kidney injury (AKI). The incidence, risk factors associations, need for dialysis and inhospital mortality related to AKI in patients with critical limb ischemia (CLI) following endovascular therapy is poorly defined. Objectives The purpose of this study was to analyze data from the National Inpatient Sample (NIS) to determine the afore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…In line with previous studies including patients who underwent coronary artery angiography and percutaneous coronary intervention, Prasad and colleagues report an overall incidence of AKI of 10.4% . However, the authors found also a steady increase in the incidence of AKI over time, especially from 2008 to 2012, when rates rose from 9.7 to 17.9% . AKI requiring dialysis occurred also with an increasing incidence over the study period .…”
supporting
confidence: 76%
See 4 more Smart Citations
“…In line with previous studies including patients who underwent coronary artery angiography and percutaneous coronary intervention, Prasad and colleagues report an overall incidence of AKI of 10.4% . However, the authors found also a steady increase in the incidence of AKI over time, especially from 2008 to 2012, when rates rose from 9.7 to 17.9% . AKI requiring dialysis occurred also with an increasing incidence over the study period .…”
supporting
confidence: 76%
“…In contrast, AKI‐related and all‐cause mortality rates declined over time . These findings are difficult to interpret and might have not been properly addressed in the study due to the limitations imposed by the design based on procedure and diagnosis codes . Indeed, changes and variable implementation of AKI definitions might have occurred during the study and the present dataset shows no information about variations of serum creatinine and urine output from baseline values, hydration status, application of preventive strategies, use of concomitant medications with effects on renal function, and remains unclear the influence of unmeasured procedural factors .…”
mentioning
confidence: 68%
See 3 more Smart Citations